Neoconservative politics and the Supreme Court : law, power, and democracy - Feldman, Stephen M., 1955- (New York : New York University Press, 2016)
In this book, constitutional law expert Stephen M. Feldman draws on neoconservative writings to explore the rise of the neocons and their influence on the Supreme Court.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Political questions and judicial power -- United States; United States. -- Supreme Court; Conservatism -- United States; Politics and Government; United States of America, USA; Politics & government; Conservatism & right-of-centre democratic ideologies; Political structures: democracy; Jurisprudence & general issues